GAMIFICAÇÃO EM AULAS DE MATEMÁTICA: um processo de integração de tecnologias digitais ao currículo. - JANINI GOMES CALDAS (2022)
This masters research was guided by the question: How a process of integrating Digital Technologies happens into the mathematics curriculum from the Gamification? The objective of this research was to analyze a proposal for the integration of Digital Technologies to the mathematics curriculum in a High School class using Gamification. The investigation was developed with the proposition and experience with gamification processes during the mathematics classes in the 1st year of High School, in a public school in the state of Mato Grosso do Sul, during the academic semester of 2021, in such a way as to provide opportunities for learning concepts related to functions. Two gamified actions were proposed and analyzed in the process of integrating digital technologies into the curriculum, the first using platforms such as Khan Academy and GeoGebra, and the second using an authorial platform. Data production was carried out remotely (due to the pandemic period), during classes and student productions, from records made by the teacher, author of this research. Data analysis was guided by theories and ideas by Sánchez and Almeida and Valente about the integration of Digital Technologies and by studies by Kapp, Alves and Busarello about Gamification. From the data analysis, it was possible conclude that Gamification provided the opportunity for students to be involved in the activities of the discipline, providing the opportunity to learn mathematical concepts related to the 1st degree equation and the squaring function. It is also possible to conclude that in the integration process experienced, the use of Digital Technologies changed ways of planning and developing math classes, in which the teaching of functions was proposed from Gamification movements.